Three-dimensional ordered macroporous alumina composite adsorbent and preparation method thereof

By co-precipitating polystyrene and alumina, macroporous alumina is prepared and polymerized with silica to form a three-dimensional ordered macroporous alumina composite adsorbent, the problem of limited adsorption capacity of existing silica gel adsorbents in high humidity environments is solved, and high efficiency dehumidification and low energy consumption regeneration are achieved.

CN119857462AInactive Publication Date: 2025-04-22HANGZHOU DRY AIR TREATMENT EQUIP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510256284.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing silicone adsorption materials have limited adsorption capacity in high humidity environments, and the adsorbed moisture during the regeneration process is difficult to desorption, resulting in low regeneration efficiency and increasing energy consumption and operating costs.

Method used

Polystyrene as a template agent and alumina particles were used to prepare macroporous alumina for co-precipitation, and polymerize it with silica to form a three-dimensional ordered macroporous alumina composite adsorbent with a pore size of 100-200nm and a BET specific surface area of ​​250-480m2/g.

Benefits of technology

Provides a large adsorption capacity in high humidity environments, improves the dehumidification effect, reduces the regeneration temperature and reduces the energy consumption of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005298459980000061
    Figure BDA0005298459980000061
  • Figure BDA0005298459980000071
    Figure BDA0005298459980000071
Patent Text Reader

Abstract

The invention relates to the field of preparation of gas adsorption and dehumidification materials, and particularly discloses a three-dimensional ordered macroporous alumina composite adsorbent and a preparation method thereof. The three-dimensional ordered macroporous aluminum oxide composite adsorbent comprises the following raw materials in parts by weight: 20-80 parts of silicon dioxide and 20-80 parts of macroporous aluminum oxide, and the macroporous aluminum oxide is prepared by adopting a method of coprecipitating polystyrene serving as a template agent and aluminum oxide particles; the macroporous aperture of the adsorbent is 100-200nm, and the BET specific surface area of the adsorbent is 250-480m < 2 > / g; the composite adsorbent prepared by the invention is uniform in particle distribution, forms an ordered three-dimensional through hole structure, and can have relatively large adsorption capacity in a high-humidity environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of gas adsorption and dehumidification material preparation, and in particular to a three-dimensional ordered macroporous alumina composite adsorbent and a preparation method thereof. Background Art

[0002] Humidity control plays a vital role in life and industrial production. In the fields of food storage, pharmaceutical production and electronic component manufacturing, too high or too low humidity may cause product deterioration, failure or reduce production efficiency. Silica gel is a widely used dehumidification material with low price and good physical and chemical stability.

[0003] At present, the commonly used silica gel adsorption materials are mainly microporous and mesoporous structures. The characteristics of this pore size make it selective for the adsorption of water vapor. However, in an environment with high relative humidity, the adsorption capacity of silica gel is often limited and cannot meet the dehumidification needs under high humidity conditions. At the same time, due to the small pore size of silica gel, the adsorbed water is difficult to desorb during the regeneration process, resulting in low regeneration efficiency, increased energy consumption and operating costs. Summary of the invention

[0004] In order to improve the adsorption performance of the adsorption material in a high humidity environment, the present application provides a three-dimensional ordered macroporous alumina composite adsorbent and a preparation method thereof.

[0005] In the first aspect, the present application provides a three-dimensional ordered macroporous alumina composite adsorbent, which adopts the following technical solution: A three-dimensional ordered macroporous alumina composite adsorbent, comprising the following raw materials in parts by weight: 20-80 parts of silicon dioxide and 20-80 parts of macroporous alumina, wherein the macroporous alumina is prepared by co-precipitation with alumina particles using polystyrene as a template; the adsorbent has a pore size of 100-200 nm and a BET specific surface area of ​​250-480 m 2 / g.

[0006] By adopting the above technical scheme, macroporous alumina prepared by co-precipitation of alumina particles with polystyrene as a template is polymerized with silica to form a macroporous adsorbent with a pore size of 100-200nm. The prepared composite adsorbent particles are evenly distributed, have a large specific surface area, and form an ordered three-dimensional through-pore structure. In an environment with high relative humidity, it can provide a large adsorption capacity, achieve the effect of adsorption and dehumidification, effectively reduce the regeneration temperature, and reduce energy consumption.

[0007] Preferably, the polystyrene template is modified by polydiallyldimethylammonium chloride.

[0008] By adopting the above technical solution and using polydiallyldimethylammonium chloride to modify the polystyrene template, the polystyrene template can have the same electrical properties as the alumina particles, thereby reducing the adsorption and aggregation of the polystyrene template and the alumina particles, and promoting the adsorbent to form through pores.

[0009] Preferably, the adsorbent raw material also includes a nonionic surfactant.

[0010] Preferably, the nonionic surfactant is fatty alcohol polyoxyethylene ether.

[0011] By adopting the above technical scheme, the fatty alcohol polyoxyethylene ether has amphiphilicity, and the polyoxyethylene chain segment in the molecule can form hydrogen bonds with the surface of silica and alumina. As silica and alumina form polymers through diffusion and adsorption, more surfactants are adsorbed on the surface of the polymer, prompting the non-ionic surfactant to form self-assembly with silica and alumina to form an ordered mesoporous structure, promote phase separation of the adsorbent system, increase the pore volume and specific surface area of ​​the adsorbent material, and increase the pore size of the adsorbent.

[0012] In a second aspect, the present application provides a method for preparing a three-dimensional ordered macroporous alumina composite adsorbent, using the following technical solution: A method for preparing a three-dimensional ordered macroporous alumina composite adsorbent comprises the following specific steps: S1: In a nitrogen atmosphere, styrene is used as a monomer, potassium persulfate is used as an initiator, and sodium bicarbonate is used as a buffer solution. The polystyrene colloidal particles are prepared by a soap-free emulsion polymerization method at 50-100°C for 15-24h; S2: adding an aluminum precursor to an organic solvent, and continuously stirring until the aluminum precursor is completely dissolved to obtain an aluminum precursor solution, adding polystyrene colloidal particles to the aluminum precursor solution, and stirring and mixing the mixture to obtain a mixed solution A; S3: Sodium silicate is added into deionized water to prepare a silicate solution with a concentration of 20-40wt.%, and the modulus of sodium silicate is 3.1-3.4. Then, the solution is added into the mixed solution A, stirred evenly at 40-80°C, and then subjected to a hydrothermal reaction at 100-200°C for 4-12h. The precipitated product obtained after the reaction is filtered, washed, dried, and calcined to obtain a three-dimensional ordered macroporous alumina composite adsorbent.

[0013] By adopting the above technical scheme, template polystyrene colloidal particles are added to the aluminum precursor to form an aluminum salt solution, and then a silicate solution is added. Alumina is used for composite modification during the formation of silica gel to obtain a three-dimensional ordered macroporous alumina composite adsorbent with a larger pore size, uniform distribution of silica gel particles, and a larger adsorption capacity.

[0014] Preferably, the aluminum precursor is at least one of aluminum sec-butoxide, aluminum triethoxide, and aluminum isopropoxide, and the organic solvent is at least one of 2-butanol and 2-isopropane.

[0015] Preferably, deionized water or anhydrous ethanol is used for washing, the roasting temperature is 300-600° C., and the roasting time is 4-10 hours.

[0016] Preferably, the method comprises the following specific steps: S1: In a nitrogen atmosphere, styrene is used as a monomer, potassium persulfate is used as an initiator, and sodium bicarbonate is used as a buffer solution. Polystyrene colloidal particles are prepared by a soap-free emulsion polymerization method at 50-100°C for 15-24 hours. The polystyrene colloidal particles are mixed with polydiallyldimethylammonium chloride, stirred evenly, and then ultrasonically dispersed. The mixture is allowed to stand for 30-40 minutes to react, the supernatant is removed by centrifugation, and the modified polystyrene colloidal particles are obtained by dispersion and washing with distilled water. S2: adding an aluminum precursor to an organic solvent, and continuously stirring until the aluminum precursor is completely dissolved to obtain an aluminum precursor solution, adding modified polystyrene colloidal particles to the aluminum precursor solution, and stirring and mixing the modified polystyrene colloidal particles to obtain a mixed solution A; S3: Sodium silicate is added into deionized water to prepare a silicate solution with a concentration of 20-40wt.%, and the modulus of sodium silicate is 3.1-3.4. Then, the solution is added into the mixed solution A, stirred evenly at 40-80°C, and then subjected to a hydrothermal reaction at 100-200°C for 4-12h. The precipitated product obtained after the reaction is filtered, washed, dried, and calcined to obtain a three-dimensional ordered macroporous alumina composite adsorbent.

[0017] Preferably, step S2 is: adding an aluminum precursor and a non-ionic surfactant to an organic solvent, wherein the mass ratio of the aluminum precursor and the non-ionic surfactant is 1:(0.05-0.1), and continuously stirring until completely dissolved to obtain an aluminum precursor solution, adding polystyrene colloidal particles to the aluminum precursor solution, and fully stirring and mixing to obtain a mixed solution A.

[0018] By adopting the above technical solution, the aluminum precursor, non-ionic surfactant, polystyrene glue and subsequent silica gel phase polymerization form a mesoporous structure material with regular structure and uniform pore size, which can improve the orderliness of the composite adsorbent. At the same time, the non-ionic surfactant enters the silica-alumina gel skeleton, which can increase the specific surface area and pore volume of the composite adsorbent and increase the pore size of the adsorbent.

[0019] In summary, this application has the following beneficial effects: 1. Since the present application uses polystyrene as a template and alumina to make macroporous alumina, and then alumina and silica are polymerized to generate aluminum-silica gel adsorbent, forming a three-dimensional ordered mesoporous structure, the pore size of the adsorbent is large and has a higher adsorption capacity in a high humidity environment.

[0020] 2. In the present application, the polystyrene template is modified with polydiallyldimethylammonium chloride, which can reduce the phenomenon of the polystyrene template and the alumina particles being adsorbed together, and promote the prepared adsorbent to form through-holes. DETAILED DESCRIPTION

[0021] The present application is further described in detail below with reference to the embodiments.

[0022] All raw materials in the examples are commercially available. Example

[0023] Example 1 This embodiment provides a three-dimensional ordered macroporous alumina composite adsorbent, comprising the following raw materials in parts by weight: 50 g of silicon dioxide and 50 g of macroporous alumina.

[0024] The preparation method of the three-dimensional ordered macroporous alumina composite adsorbent comprises the following specific steps: S1: Under nitrogen atmosphere, styrene is used as monomer, potassium persulfate is used as initiator, 20wt.% sodium bicarbonate aqueous solution is used as buffer solution, the mass ratio of styrene, initiator and sodium bicarbonate aqueous solution is 1:0.02:0.4, stir evenly, polymerize at 80℃ for 20h, and obtain polystyrene colloidal particles after centrifugation.

[0025] S2: Add an aluminum precursor to an organic solvent, wherein the aluminum precursor is aluminum isopropoxide, the organic solvent is 2-butanol, and the mass ratio of the aluminum precursor to the organic solvent is 1:3. Continue stirring until completely dissolved to obtain an aluminum precursor solution. Add polystyrene colloid particles to the aluminum precursor solution, stir and mix thoroughly to obtain a mixed solution A, wherein the volume ratio of polystyrene colloid particles to alumina is 1:1.

[0026] S3: Sodium silicate with a modulus of 3.2 is added to deionized water to prepare a silicate solution with a concentration of 30wt.%, and then the silicate solution is added to the mixed solution A. After stirring at 60°C for 5h, a hydrothermal reaction is carried out at 150°C for 8h to obtain a silica-macroporous alumina composite with a silica weight of 50g and a macroporous alumina weight of 50g. The composite is filtered, washed with deionized water, dried at 70°C for 17h, and calcined at 450°C for 7h to obtain a three-dimensional ordered macroporous alumina composite adsorbent. The macropore diameter of the composite adsorbent is 156nm, and the BET specific surface area is 375m 2 / g.

[0027] Example 2 The difference between Example 2 and Example 1 is that in the preparation of the three-dimensional ordered macroporous alumina composite adsorbent, the weight ratio of silica to macroporous alumina in the silica-macroporous alumina composite is 80:20.

[0028] Example 3 The difference between Example 3 and Example 1 is that in the preparation of the three-dimensional ordered macroporous alumina composite adsorbent, the weight ratio of silica to macroporous alumina in the silica-macroporous alumina composite is 20:80.

[0029] Example 4 The difference between Example 4 and Example 1 is that the aluminum precursor in the preparation of the three-dimensional ordered macroporous alumina composite adsorbent is triethoxy aluminum.

[0030] Example 5 The difference between Example 5 and Example 1 is that in the preparation of the three-dimensional ordered macroporous alumina composite adsorbent, the polystyrene template is modified by polydiallyldimethylammonium chloride, and the molecular weight of the polydiallyldimethylammonium chloride is 200,000.

[0031] The preparation method of the three-dimensional ordered macroporous alumina composite adsorbent comprises the following specific steps: S1: Under nitrogen atmosphere, styrene is used as monomer, potassium persulfate is used as initiator, 20wt.% sodium bicarbonate aqueous solution is used as buffer solution, the mass ratio of styrene, initiator and sodium bicarbonate aqueous solution is 1:0.02:0.4, and the mixture is stirred evenly, and polymerized at 80°C for 20h to obtain polystyrene colloidal particles; the polystyrene colloidal particles are mixed with 1% polydiallyldimethylammonium chloride aqueous solution, the mass ratio of polystyrene colloidal particles to polydiallyldimethylammonium chloride is 1:0.05, stirred evenly, and then ultrasonically dispersed for 6min, allowed to stand for 35min to react, centrifuged to remove the supernatant, and dispersed and washed with distilled water to obtain modified polystyrene colloidal particles.

[0032] S2: Add an aluminum precursor to an organic solvent, wherein the aluminum precursor is aluminum isopropoxide, the organic solvent is 2-butanol, and the mass ratio of the aluminum precursor to the organic solvent is 1:3. Continue stirring until completely dissolved to obtain an aluminum precursor solution. Add modified polystyrene colloid particles to the aluminum precursor solution, stir and mix thoroughly to obtain a mixed solution A, wherein the volume ratio of the modified polystyrene colloid particles to alumina is 1:1.

[0033] S3: Sodium silicate with a modulus of 3.2 is added to deionized water to prepare a silicate solution with a concentration of 30wt.%, and then the silicate solution is added to the mixed solution A. After stirring at 60°C for 5 hours, a hydrothermal reaction is carried out at 150°C for 8 hours to obtain a silica-macroporous alumina composite, in which the weight ratio of silica to macroporous alumina is 50:50. The composite is filtered, washed with deionized water, dried at 70°C for 17 hours, and calcined at 450°C for 7 hours to obtain a three-dimensional ordered macroporous alumina composite adsorbent. The macropore diameter of the composite adsorbent is 185nm, and the BET specific surface area is 452m 2 / g.

[0034] Example 6 The difference between Example 6 and Example 5 is that the preparation method of the three-dimensional ordered macroporous alumina composite adsorbent comprises the following specific steps: S1: Under nitrogen atmosphere, styrene is used as monomer, potassium persulfate is used as initiator, 20wt.% sodium bicarbonate aqueous solution is used as buffer solution, the mass ratio of styrene, initiator and sodium bicarbonate aqueous solution is 1:0.02:0.4, and the mixture is stirred evenly, and polymerized at 80°C for 20h to obtain polystyrene colloidal particles; the polystyrene colloidal particles are mixed with 1% polydiallyldimethylammonium chloride aqueous solution, the mass ratio of polystyrene colloidal particles to polydiallyldimethylammonium chloride is 1:0.05, stirred evenly, and then ultrasonically dispersed for 6min, allowed to stand for 35min to react, centrifuged to remove the supernatant, and dispersed and washed with distilled water to obtain modified polystyrene colloidal particles.

[0035] S2: Add an aluminum precursor and a nonionic surfactant to an organic solvent, the mass ratio of the aluminum precursor to the nonionic surfactant is 1:0.08, the nonionic surfactant is fatty alcohol polyoxyethylene ether AEO-9, the aluminum precursor is aluminum isopropoxide, the organic solvent is 2-butanol, and the mass ratio of the aluminum precursor to the organic solvent is 1:3, and continue stirring until completely dissolved to obtain an aluminum precursor solution, add the modified polystyrene colloidal particles to the aluminum precursor solution, stir and mix thoroughly to obtain a mixed solution A, in which the volume ratio of the modified polystyrene colloidal particles to alumina is 1:1.

[0036] S3: Sodium silicate with a modulus of 3.2 is added to deionized water to prepare a silicate solution with a concentration of 30wt.%, and then the silicate solution is added to the mixed solution A. After stirring at 60°C for 5 hours, a hydrothermal reaction is carried out at 150°C for 8 hours to obtain a silica-macroporous alumina composite, in which the weight ratio of silica to macroporous alumina is 50:50. The composite is filtered, washed with deionized water, dried at 70°C for 17 hours, and calcined at 450°C for 7 hours to obtain a three-dimensional ordered macroporous alumina composite adsorbent. The macropore diameter of the composite adsorbent is 200nm, and the BET specific surface area is 480m 2 / g.

[0037] Example 7 The difference between Example 7 and Example 6 is that in the preparation of the three-dimensional ordered macroporous alumina composite adsorbent, the mass ratio of the aluminum precursor to the non-ionic surfactant is 1:0.05.

[0038] Example 8 The difference between Example 8 and Example 6 is that in the preparation of the three-dimensional ordered macroporous alumina composite adsorbent, the mass ratio of the aluminum precursor to the non-ionic surfactant is 1:0.1.

[0039] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no silicon dioxide is used in the raw material of the three-dimensional ordered macroporous alumina composite adsorbent.

[0040] The preparation method of the three-dimensional ordered macroporous alumina composite adsorbent comprises the following specific steps: S1: Under nitrogen atmosphere, styrene is used as monomer, potassium persulfate is used as initiator, 20wt.% sodium bicarbonate aqueous solution is used as buffer solution, the mass ratio of styrene, initiator and sodium bicarbonate aqueous solution is 1:0.02:0.4, stir evenly, polymerize at 80℃ for 20h, and obtain polystyrene colloidal particles after centrifugation.

[0041] S2: Add an aluminum precursor to an organic solvent, wherein the aluminum precursor is aluminum isopropoxide, the organic solvent is 2-butanol, and the mass ratio of the aluminum precursor to the organic solvent is 1:3. Stir continuously until completely dissolved to obtain an aluminum precursor solution. Add polystyrene colloidal particles to the aluminum precursor solution, stir and mix thoroughly to obtain a mixed solution A, wherein the volume ratio of polystyrene colloidal particles to alumina is 1:1. Filter, wash with deionized water, dry at 70°C for 17h, and calcine at 450°C for 7h to obtain a macroporous alumina adsorbent. The macropore diameter of the macroporous alumina adsorbent is 300nm, and the BET specific surface area is 210m 2 / g, diffuse large pores appear, and the three-dimensional permeability is poor.

[0042] Performance testing According to the three-dimensional ordered macroporous alumina composite adsorbent provided in Examples 1-8 and Comparative Example 1 of the present application, the following performance tests were carried out, and the specific test results are shown in Table 1.

[0043] Detection Methods 1. Appearance The three-dimensional penetration of the pore size, pore volume and porosity of the composite adsorbent prepared in the present application were observed by scanning electron microscopy and specific surface area analysis tester.

[0044] 2. Adsorption and dehumidification effect The three-dimensional ordered macroporous alumina composite adsorbent prepared in the present application was placed under the test conditions of wind speed of 1.5 m / s, temperature of 25°C, and relative humidity of 80% for fixed adsorption for 30 minutes, and the moisture absorption rate of the adsorbent was measured. The moisture absorption rate = (mass after adsorption for 30 minutes - original mass of the adsorbent sample) / original mass of the adsorbent sample.

[0045] Table 1: Performance test results data table From the performance test results, it can be seen that the composite adsorbent prepared in the present application has a good three-dimensional ordered macroporous structure, the macropores are evenly distributed, the macropore porosity reaches about 70%, and it also has a good adsorption capacity, which can better achieve a dehumidification effect in a high humidity environment.

[0046] It can be seen from Examples 5-6 that in Example 5, the polystyrene template is modified using polydiallyldimethylammonium chloride. From the performance test results, it can be seen that the porosity and macropore diameter of the adsorbent are significantly improved, and the adsorption amount is also improved, further indicating that polydiallyldimethylammonium chloride can effectively improve the adsorbent to form through ordered channels. The preparation of the composite adsorbent in Example 6 also includes a nonionic surfactant, and the pore structure of the prepared adsorbent is further optimized.

[0047] By comparing Comparative Example 1 with Example 1, it can be seen that Comparative Example 1 uses conventional macroporous alumina. Although the prepared adsorbent has a macroporous structure, the macroporous structure is distributed in a disorderly manner, the three-dimensional permeability is poor, and the appearance is a loose powder, which results in the inability to achieve the effect of adsorption and dehumidification in a high humidity environment.

[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A three-dimensional ordered macroporous alumina composite adsorbent, characterized in that: The invention comprises the following raw materials in parts by weight: 20-80 parts of silicon dioxide and 20-80 parts of macroporous alumina, wherein the macroporous alumina is prepared by co-precipitation of polystyrene as a template with alumina particles; the macropore diameter of the adsorbent is 100-200 nm, and the BET specific surface area is 250-480 m 2 / g.

2. The three-dimensional ordered macroporous alumina composite adsorbent according to claim 1, characterized in that: The polystyrene template is modified by polydiallyldimethylammonium chloride.

3. The three-dimensional ordered macroporous alumina composite adsorbent according to claim 1, characterized in that: The adsorbent raw material also includes a nonionic surfactant.

4. The three-dimensional ordered macroporous alumina composite adsorbent according to claim 3, characterized in that: The nonionic surfactant is fatty alcohol polyoxyethylene ether.

5. A method for preparing the three-dimensional ordered macroporous alumina composite adsorbent according to any one of claims 1 to 4, characterized in that: The specific steps include: S1: In a nitrogen atmosphere, styrene is used as a monomer, potassium persulfate is used as an initiator, and sodium bicarbonate is used as a buffer solution. Polystyrene colloidal particles are prepared by a soap-free emulsion polymerization method at 50-100°C for 15-24 hours; the mass ratio of styrene, initiator, and sodium bicarbonate is 1: (0.01-0.03): (0.3-0.5); S2: adding an aluminum precursor to an organic solvent, stirring continuously until completely dissolved, to obtain an aluminum precursor solution, adding polystyrene colloidal particles to the aluminum precursor solution, stirring and mixing sufficiently, to obtain a mixed solution A, wherein the volume ratio of polystyrene colloidal particles to alumina in the mixed solution is 1:(0.8-1.2); S3: Sodium silicate is added into deionized water to prepare a silicate solution with a concentration of 20-40wt.%, and the modulus of sodium silicate is 3.1-3.

4. Then, the solution is added into the mixed solution A, stirred evenly at 40-80°C, and then subjected to a hydrothermal reaction at 100-200°C for 4-12h. The precipitated product obtained after the reaction is filtered, washed, dried, and calcined to obtain a three-dimensional ordered macroporous alumina composite adsorbent.

6. The method for preparing the three-dimensional ordered macroporous alumina composite adsorbent according to claim 5, characterized in that: The aluminum precursor is at least one of aluminum sec-butoxide, aluminum triethoxide, and aluminum isopropoxide, and the organic solvent is at least one of 2-butanol and 2-isopropane.

7. The method for preparing the three-dimensional ordered macroporous alumina composite adsorbent according to claim 5, characterized in that: Deionized water or anhydrous ethanol is used for washing, the roasting temperature is 300-600° C., and the roasting time is 4-10 hours.

8. The method for preparing the three-dimensional ordered macroporous alumina composite adsorbent according to claim 5, characterized in that: The specific steps include: S1: In a nitrogen atmosphere, styrene is used as a monomer, potassium persulfate is used as an initiator, and sodium bicarbonate is used as a buffer solution. Polystyrene colloidal particles are prepared by a soap-free emulsion polymerization method at 50-100°C for 15-24 hours. The polystyrene colloidal particles are mixed with polydiallyldimethylammonium chloride, stirred evenly, and then ultrasonically dispersed. The mixture is allowed to stand for 30-40 minutes to react, the supernatant is removed by centrifugation, and the modified polystyrene colloidal particles are obtained by dispersion and washing with distilled water. S2: adding an aluminum precursor to an organic solvent, and continuously stirring until the aluminum precursor is completely dissolved to obtain an aluminum precursor solution, adding modified polystyrene colloidal particles to the aluminum precursor solution, and stirring and mixing the modified polystyrene colloidal particles to obtain a mixed solution A; S3: Sodium silicate is added into deionized water to prepare a silicate solution with a concentration of 20-40wt.%, and the modulus of sodium silicate is 3.1-3.

4. Then, the solution is added into the mixed solution A, stirred evenly at 40-80°C, and then subjected to a hydrothermal reaction at 100-200°C for 4-12h. The precipitated product obtained after the reaction is filtered, washed, dried, and calcined to obtain a three-dimensional ordered macroporous alumina composite adsorbent.

9. The method for preparing the three-dimensional ordered macroporous alumina composite adsorbent according to claim 5, characterized in that: The step S2 is: adding an aluminum precursor and a non-ionic surfactant to an organic solvent, wherein the mass ratio of the aluminum precursor to the non-ionic surfactant is 1:(0.05-0.1), and continuously stirring until completely dissolved to obtain an aluminum precursor solution, adding polystyrene colloidal particles to the aluminum precursor solution, and fully stirring and mixing to obtain a mixed solution A.